THE INFLUENCE OF SOCIAL MEDIA MARKETING AND BRAND AWARENESS ON CAFE YUMA BANDUNG PURCHASE DECISIONS - Frans Sudirjo; I Nyoman Tri Sutaguna; Endang Silaningsih; Farida Akbarina; Muhammad Yusuf (Universitas 45 Surabaya, 2023)
This study employs quantitative and descriptive methods.